INOVASI ANJAS GO CLEAR BERBASIS MERIT SYSTEM DAN KOMPETENSI UNTUK MENCEGAH INTERVENSI PENEMPATAN PEJABAT - Joko Tri Nugraha (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2020)
Innovation in government organizations is a transformation of the main functions of the organization and permanent and fundamental changes in the organizational structure. Meritocracy in the system of placing officials at the central and regional levels is an urgent need. However, today meritocracy is still at the level of discourse that needs to be fought. There are many obstacles surrounding the achievement of a merit official placement system. Political obstacles still revolve around configurations that reduce spoil loyalty between elected officials and their supporters. The culture of nepotism that is still thick in the public bureaucratic system, money politics, also adds to the barriers to the ongoing merit system. The purpose of writing this article is to describe one form of public sector innovation that aims to prevent intervention in the placement public officials. The method used is descriptive qualitative method using researchers as a tool based on library studies. With regard to the level of innovation that reflects the magnitude of the impact caused by ongoing innovation, Anjas Go Clear, which is an Innovation from the City of Bogor to prevent intervention in the placement of officials including in service creation innovation, process innovation, administrative innovation and system innovation.